2010
DOI: 10.1002/jor.21219
|View full text |Cite
|
Sign up to set email alerts
|

Low dose erythropoietin stimulates bone healing in mice

Abstract: Beyond its classical role in regulation of erythropoiesis, erythropoietin (EPO) has been shown to exert protective and regenerative actions in a variety of non-hematopoietic tissues. However, little is known about potential actions in bone regeneration. To analyze fracture healing in mice, a femoral 0.25 mm osteotomy gap was stabilized with a pin-clip technique. Animals were treated with 500 U EPO/kg bw per day or with vehicle only. After 2 and 5 weeks, fracture healing was analyzed biomechanically, radiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 35 publications
6
58
0
Order By: Relevance
“…In agreement with the findings of this thesis, the majority of the published pre-clinical studies document an advantageous effect of EPO on early bone healing (Holstein et al 2007;Garcia et al 2011;. Taken together with the first data from a clinical trial, these findings indicate an improved healing process and (Bakhshi et al 2013).…”
Section: The Effect Of Epo On Bone Healingsupporting
confidence: 86%
“…In agreement with the findings of this thesis, the majority of the published pre-clinical studies document an advantageous effect of EPO on early bone healing (Holstein et al 2007;Garcia et al 2011;. Taken together with the first data from a clinical trial, these findings indicate an improved healing process and (Bakhshi et al 2013).…”
Section: The Effect Of Epo On Bone Healingsupporting
confidence: 86%
“…It was reported that Epo at a dose of 500 U/kg significantly increased the fracture healing in a mouse femoral osteotomy model. 47 However, 300 U/kg and 10-day intraperitoneal injection of Epo was found to decrease the trabecular BV in mouse tibia. 46 Therefore, the dosage, duration, and route for Epo administration, and the anatomic site of bone to be regenerated may also be important considerations for the application of Epo for bone tissue engineering.…”
Section: Fig 3 Epo Increased Osteoclastogenesis In Vivo and In Vitromentioning
confidence: 93%
“…23 Recently, one group reported Epo to improve long bone healing, possibly due to its angiogenic effects. 47,58,59 Despite these findings, the role of Epo in bone repair remains largely unknown.…”
Section: Fig 3 Epo Increased Osteoclastogenesis In Vivo and In Vitromentioning
confidence: 99%
“…The role of EPO in non-hematopoietic cells includes promotion of endothelial cell proliferation (Anagnostou et al, 1994), protection of myocardial injury caused by myocardial infarction (Kagaya et al, 2012), inhibition of ventricular remodeling induced by angiotensin II (Zhang et al, 2009), and improvement of the recovery of damaged nerve cells (Sirén et al, 2001). In addition, EPO can inhibit inflammatory factors and promote fracture healing (Garcia et al, 2011) by reducing the expression of nuclear factor-kB. Hojman et al (2009) demonstrated that EPO can inhibit the weight gain of mice induced by a high-fat diet, while mice lacking EPO-R expression are more likely to gain fat and develop insulin resistance.…”
Section: Introductionmentioning
confidence: 99%